Effectiveness of Principal’s Academic Supervision Model in Improving Teachers’ Competency: A Systematic Literature Review - Lara, Erni Siti; Wardiah, Dessy; Suherman, Suherman (Journal of Social Work and Science Education, 2025)
This study aims to analyze the effectiveness of academic supervision models implemented by school principals in improving teacher competence through a systematic literature review approach. The review compiles and examines various previous studies discussing the implementation of academic supervision and its impact on teacher professionalism and the quality of learning. Supervision that is conducted systematically and based on evaluation has been proven to enhance instructional quality, teacher well-being, and overall organizational performance in education. The findings of this study highlight the critical role of school leadership, particularly in developing contextual and sustainable supervision strategies. This research contributes to the development of adaptive and applicable academic supervision strategies that align with current educational dynamics.